2012
DOI: 10.3390/ijms131114311
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Ischemia-Induced Oxidative Stress Conferred by Vagal Stimulation in the Rat Heart: Involvement of the AMPK-PKC Pathway

Abstract: Reactive oxygen species (ROS) production is an important mechanism in myocardial ischemia and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is one of major sources of ROS in the heart. Previous studies showed that vagus nerve stimulation (VNS) is beneficial in treating ischemic heart diseases. However, the effect of VNS on ROS production remains elusive. In this study, we investigated the role of VNS onischemia-induced ROS production. Our results demonstrated that VNS alleviated the myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 32 publications
6
49
0
Order By: Relevance
“…Our results have indicated that ACh have a protective role in resistance to H/R-induced oxidative stress through the regulation of antioxidant gene SOD. Such a finding is in agreement with our recent study, showing that VNS enhanced the expressions of SOD1 and SOD2 in rat myocardium after myocardial infarction [28]. In addition to SOD, other antioxidants like catalase and glutathione reductase, also play important roles in ROS scavenging.…”
Section: Discussionsupporting
confidence: 82%
“…Our results have indicated that ACh have a protective role in resistance to H/R-induced oxidative stress through the regulation of antioxidant gene SOD. Such a finding is in agreement with our recent study, showing that VNS enhanced the expressions of SOD1 and SOD2 in rat myocardium after myocardial infarction [28]. In addition to SOD, other antioxidants like catalase and glutathione reductase, also play important roles in ROS scavenging.…”
Section: Discussionsupporting
confidence: 82%
“…Based on previous reports, the reduction of ROS during cholinergic modulation could be a result of increased reducing-enzyme(s) activity or inhibition of ROS generation through NADPH oxidase, xanthine oxidase and mitochondria. 6567 …”
Section: Discussionmentioning
confidence: 99%
“…Ekici et al (23) demonstrated that VS exhibits antioxidant efficacy in the treatment of focal cerebral I/R; therefore VS may be capable of suppressing the generation of reactive oxygen species (ROS) in ischemic heart diseases (24,25). VS may also exert its antioxidant effects by suppressing the prolonged opening of the permeable transition pore which promotes the production of ROS (16).…”
Section: Discussionmentioning
confidence: 99%